The impact of Asean free trade area (AFTA) on the information technology (IT) industry in Malaysia / Irzan Ismail - Ismail, Irzan (Universiti Teknologi MARA Cawangan Pahang, 2002)
The trends in global IT in the new millennium are irreversible, and it is imperative that we study them and address them in a serious and concerted manner. The beginning of the new millennium marks a new era in global information technology and its management. While the eighties and the nineties witnessed global business and global IT expansion, the issues in global IT have now reached a new level of interest and maturity. The introduction of the free trade area concept has somehow influences the IT industry. As we can see now that globalisation has now become a threat to every industry. These industries are either directly or indirectly affected by such rapid development in the world economy. IT is one area that is so vital to organizations where the capability to control information will give them a competitive advantage in the business environment. Global IT management is the new paradigm of the next millennium; domestic IT and urn-national IS are now only parts of the broader global IT, and it is absolutely essential that we view all aspects of IT and IS from the comprehensive and all-embracing lens of global IT management and the impact of the free trade concept on the industry.